Tantangan Implementasikan Pendekatan TaRL untuk Meningkatkan Kemampuan Matematis Siswa - Deny Hadi Siswanto; Tarso Tarso; Siti Atwano Pisriwati (Academicus: Journal of Teaching and Learning, 2025)
This study aims to identify problems in the field by describing the challenges faced by teachers in implementing the Teaching at the Right Level (TaRL) approach to mathematics learning in class X-A. This study uses a qualitative descriptive method. The data analyzed includes primary and secondary data collected through interviews, observations, and documentation. The data analysis process includes the stages of data reduction, data presentation, and drawing conclusions, while the validity of the data is tested using triangulation techniques. The results of the study revealed a number of challenges in implementing the TaRL approach, namely: (1) lack of teacher understanding of the TaRL concept and techniques, (2) a heterogeneous classroom environment with 30 students, (3) limited time, costs, and monitoring of learning implementation, (4) minimal resources such as learning devices, and (5) limited training and socialization related to learning planning and evaluation with the TaRL approach. To overcome these challenges, schools or principals need to provide support in the form of training on the TaRL learning approach for teachers, as well as provide adequate facilities, learning resources, and budget allocations that support the implementation of learning.